Peningkatan Produktivitas, Pemasaran Digital, dan Pembukuan Sederhana Berbasis IT Usaha Konveksi di Desa Lengkong Kabupaten Bandung - Basuki, Teguh Iman; Puryati, Dwi; Kuntadi, Susinah (Jurnal Pengabdian Tri Bhakti, 2021)
This PKM aims to help people who already have a business to produce fashion products (conventions). The partner in this program is Mr. Muchlis, a convection business actor located in Lengkong village, Bandung district. The problems faced by partners are (1) The length of the process of making buttonholes and installing buttons because they do not have a special machine for making buttonholes, so that they are transferred to other parties (2) Do not understand and have an adequate bookkeeping system resulting in difficulties in recording and calculating raw materials, wages, labor, other production costs, inaccurate determination of selling prices and profit calculations as well as preparation of financial reports, (3) Marketing of products is still limited and carried out offline, even though market opportunities for products are still open. The solutions offered to business partners are (1) Procurement of buttonhole making machines, (2) Making and training of IT-based bookkeeping, and (3) Making and training of social media for digital marketing, while the output targets to be produced are publication of PKM results in ISSN national journals, and media mass electronics, activity video publications, buttonhole machines, accounting systems ansi based IT, and digital marketing media.